Ekstraksi dan Identifikasi Komponen Utama Pasir Putih dari Pantai Tanjung Woka di Kabupaten Bolaang Mongondow Timur dengan Pengujan XRF - Lenak, Ketsya D; Rampe, Meytij J (General Chemistry Journal, 2023)
A goal of this research is to study the process of extracting the quartz from Pantai Tanjung Woka and component identification using XRF testing. Before the completion, the sand has smoothed first with mortar and pestling, then sifted with a 40 mesh sieve, soaked with the HCL 20% for 12 hours to dissolve the contaminating compound, washed with the aquades until the neutral pH was obtained and then dried. Sand grains are further processed by alkali fusion method in this case by NaOH 7M soldering, crystallized sodium silicate, and then titration with HCL 2M until pH neutral, and the finished product of silicate porridge Si(OH4), in turn, was dried for two days until silica filings were obtained. Tthe results of XRF test, SiO2 content on quartz is 6.33%, while the largest building block were CaO 91.04% and the other components SrO and Fe2O3 at more than 1% while the other compilers were less than 0.01%.